Impact of temperature and in situ FeCo catalysis on the architecture and Young's modulus of model wood-based biocarbon. Issue 8 (6th April 2021) - Codou, Amandine; Pin, Jean-Mathieu; Misra, Manjusri; Mohanty, Amar K.
Abstract : Effect of the pyrolysis protocol into the structure, porosity and surface Young's modulus of Pine and Maple based biocarbon. Abstract : A systematic comparison of biocarbon from hardwood (maple) and softwood (pine) as well as individual cellulose, lignin and xylan (referred to hemicellulose) was performed. For the first time, the effects of pyrolysis temperature and in situ catalysis with iron(iii ) and cobalt(ii ) nitrates were explored with the aim to determine the impact of these parameters on the final physico-chemical characteristics of the biocarbon. Relationships between the catalyzed versus non-catalyzed biocarbon, with respect to the carbonaceous structure, biocarbon porosity, and surface Young's modulus were highlighted. Between 700 and 900 °C, catalyzed biocarbon exhibited a surface morphology transition from a smooth to a corrugated surface impacting both the porosity distribution and modulus measurement. This specific morphology has been imputed to a colloidal fractal self-assembly mechanism of graphite coated FeCo nanoparticles.